Treating patients with Dynamic Wave Arc: First clinical experience. Issue 3 (March 2017) - Burghelea, Manuela; Verellen, Dirk; Dhont, Jennifer; Hung, Cecilia; Gevaert, Thierry; Van den Begin, Robbe; Collen, Christine; Poels, Kenneth; Tournel, Koen; Boussaer, Marlies; Jaudet, Cyril; Reynders, Truus; et al.
Abstract: Background and purpose: Dynamic Wave Arc (DWA) is a system-specific noncoplanar arc technique that combines synchronized gantry-ring rotation with D-MLC optimization. This paper presents the clinical workflow, quality assurance program, and reports the geometric and dosimetric results of the first patient cohort treated with DWA. Methods and materials: The RayStation TPS was clinically integrated on the Vero SBRT platform for DWA treatments. The first 15 patients treated with DWA represent a broad range of treatment sites: breast boost, prostate, lung SBRT and bone metastases, which allowed us to explore the potentials and assess the limitations of the current DWA site-specific template solution. For the DWA verification a variety of QA equipment was used, from 3D diode array to an anthropomorphic end-to-end phantom. The geometric accuracy of each arc was verified with an independent orthogonal fluoroscopy method. Results: The average beam-on delivery time was 3 min, ranging from 1.22 min to 8.82 min. All patient QAs passed our institutional clinical criteria of gamma index. For both EBT3 film and Delta4 measurements, DWA planned versus delivered dose distributions presented an average agreement above 97%. An overall mean gantry-ring geometric deviation of −0.03° ± 0.46° and 0.18° ± 0.26° was obtained, respectively. Conclusion: For the first time, DWA has been translated into the clinic and used to treat various treatment sides. DWA has been successfully added to the noncoplanar rotational IMRT techniques arsenal, allowing additional flexibility in dose shaping while preserving dosimetrically robust delivery.